PENINGKATAN PENGETAHUAN SISWA SMK NEGERI 5 KENDARI MELALUI SOSIALISASI PEMILIHAN KOSMETIK YANG BAIK DAN AMAN - Vica Aspadiah; Sabarudin Sabarudin; Wa Ode Sitti Zubaydah; Muhammad Farid Hamuni; Wianda Puspo Negoro; Refky Caesar Karangan; Talitha Nayla Shabira Rivai; Tsaqila Aulia Sukma; Wanda Januarty Saputri; Dhealfa Azzahra; Theyuci Marchelda; Rahmat Muliadi; Nur Illiyyin Akib; Halik Halik; Astrid Indalifiany; Asniar Pascayantri (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The rampant circulation of illegal cosmetics and low cosmetic safety literacy remain a problem among adolescents, increasing the risk of exposure to hazardous substances such as mercury and hydroquinone. In response, the Pharmacy Professional Education Study Program at Halu Oleo University, in collaboration with BPOM, conducted a community service activity at SMK Negeri 5 Kendari to improve students knowledge in choosing safe cosmetics. The activity was carried out through socialization and counseling using visual media, product inspection practices using the BPOM Mobile application, and the application of the KLIK (Packaging, Label, Distribution Permit, and Expiration) checking method. Evaluation was carried out through pre- and post-tests. The results of the activity showed an increase in students' understanding in recognizing safe cosmetics and high enthusiasm from the participants. This activity emphasized the importance of continuing education to develop critical and safety-conscious cosmetic consumers